Assessment of low plasma concentrations of apixaban in the periprocedural setting. (16th April 2020) - Lessire, Sarah; Dincq, Anne‐Sophie; Siriez, Romain; Pochet, Lionel; Sennesael, Anne‐Laure; Vornicu, Ovidiu; Hardy, Michael; Deceuninck, Olivier; Douxfils, Jonathan; Mullier, François
Abstract: Introduction: Estimation of residual apixaban plasma concentrations may be requested in the management of emergencies. This study aims at assessing the performance of specific anti‐Xa assays calibrated with apixaban on real‐life samples with low apixaban plasma concentrations (<30 ng/mL) and on‐treatment ranges, with and without interference of low‐molecular‐weight heparin (LMWH). Methods: The performance of the STA ® ‐Liquid Anti‐Xa assay (STA ® LAX) and the low and normal procedures of the Biophen ® Direct Factor Xa Inhibitors (DiXaI) assay was tested on 134 blood samples, collected from patients on apixaban, wherefrom 74 patients received LMWH after apixaban cessation. The results were compared with the liquid chromatography coupled with tandem mass spectrometry (LC‐MS/MS) measurements. Results: The Biophen ® DiXaI, Biophen ® DiXaI LOW, and STA ® LAX showed very good correlation with LC‐MS/MS measurements in patients without LMWH administration (Spearman r .95, .99, and .98, respectively). Their limits of quantitation were defined at 48, 24, and 12 ng/mL, respectively. The Bland‐Altman test measured mean bias (SD) at 5.6 (13.1), −2.5 (5.0), and −0.8 (6.1) ng/ml, respectively. The Spearman r of the Biophen ® DiXaI decreased to 0.64 in presence of low apixaban concentrations. The Spearman r of the Biophen ® DiXaI LOW and STA ® LAX decreased to 0.39 and 0.26, respectively, in presence of LMWH. Conclusions: The accuracy of the low methodologies (Biophen ® DiXaI LOW and STA ® LAX) is slightly improved for low apixaban plasma concentrations, compared with the normal procedure of Biophen ® DiXaI. The interference of LMWH on the low methodologies is measurable, however, less important than the previously reported interference of LMWH on rivaroxaban calibrated specific anti‐Xa assays.